Comparison of Microphysics Schemes on WRF-HAILCAST Model to Study Hailstone in Aeronautics (Case Study: Hail Strike on AirAsia A320-200, November 16, 2018) - Maulana, Muhammad Ikko Safrilda; Kristianto, Aries (Universitas Negeri Malang, 2023)
A hail strike is caused by the hail phenomenon, an aviation accident caused by environmental factors. Hail is a type of extreme weather in the form of precipitation ice grains which is generally caused by cumulonimbus clouds. Research on hail modeling can be carried out using the Weather Research Forecasting Hail Forecast (WRF-HAILCAST), which can model the structure, dynamics, microphysics, hailstone distribution, and estimate the maximum diameter of the hailstone. In this study, the hail modeling that caused the hail strike on the AirAsia A320-200 aircraft on November 16, 2018, was carried out using the WRF-HAILCAST model with six different microphysics schemes. This study compares the results of the microphysics scheme on the WRF-HAILCAST model in hail modeling. The results of this study indicated that each microphysics scheme produces a different outcome. Generally, the spatial and temporal distribution of the entire scheme could indicate the presence of convective clouds reaching 40–55 dBZ. Each scheme showed the microphysical processes of clouds consisting of different hydrometeor particles. However, only MY2 and NSSL showed the presence of supercooled water, and those schemes could estimate maximum diameter hailstone worth 25.8 mm and 13.2 mm. So, NSSL is the best microphysics scheme in this study.DOI: 10.17977/um024v8i12023p020